Impact of Daily Habits on Bone Mass Density: A Study on Protein Intake, Physical Activity, and Caffeine Consumption in Indonesian Society - Christian Junus Huwae, Thomas Erwin; Irmansyah Irsan, Istan; Asmiragani, Syaifullah; Sananta, Panji; Phatama, Krisna Yuarno; Garis Herwanto, Muhammad; Cahyani, Revanda Annisa; Almadita, Teresa (Journal of Neonatal Surgery, 2025)
Introduction: Bone mass density is the total weight of bone tissue in the human body. Osteopenia, a decrease in bone mass density, is globally affected. Lifestyle and daily habits play a crucial role in bone health. This study aims to determine the relationship between daily habits in physical activity, protein intake, caffeine consumption, and bone mass density. Method: This study is an analytical-observational cross-sectional study conducted from May to July 2024 in Kendalpayak Village involving 42 participants aged 30-70 who underwent a bone mass density examination using Quantitative Ultrasound. Data was collected through questionnaire-based interviews. Data analysis was conducted using chi-square, and the results were considered significant if p-value < 0.05. Results: Type (0.014), intensity (0.037), and duration (0.001) of physical activity related to bone mass density (p-value < 0.05). While protein intake, frequency of physical activity, and caffeine consumption are not. Discussion: The study found no significant relationship between protein intake and bone mass density despite factors like calcium, vitamin D, phosphorus intake, hormonal factors, heredity, and race not being studied. Physical activity, such as weight training and high-intensity exercise, is related to bone mass density, with variation and intensity playing a more significant role. Coffee consumption did not significantly impact bone mass density, as the polyphenol content in the tea or coffee cannot be determined. Conclusion: Type, intensity, and duration of physical activity were related to bone mass density, while protein intake, frequency, and caffeine consumption were not.